Lysis profile and preference of Myxococcus sp. PT13 for typical soil bacteria - Yang, Yi; Tao, Hong; Ma, Wenwen; Wang, Nana; Chen, Xiaolin; Wang, Wenhui (Frontiers in Microbiology, 2023)
Introduction Myxococcus sp. PT13 is a wild strain with multiple predatory properties that prey on multiple model microorganisms preserved in the laboratory. However, the lysis spectrum of PT13 on typical soil bacteria and its driving effect on soil microecosystems are still unclear. Methods In this study, the lawn predation method was used to determine the predation diameter of 62 typical soil bacteria by myxobacteria PT13 and analyze their lysis spectra. Results and Discussion The results showed that PT13 had a predation diameter greater than 15 mm against typical soil microorganisms such as Aeromonas, Bacillus, Brevibacterium, Fictibacillus, Glutamicibacter, Herbaspirillum, and Leifsonia and had an outstanding lysis effect but a significant preference (p < 0.05). Absolute high-throughput sequencing results showed that PT13 predation drove the microcosmic system composed of 16 bacterial genera, with a significant decrease in the Shannon index by 11.8% (CK = 2.04, D = 1.80) and a significant increase in the Simpson index by 45.0% (CK = 0.20, D = 0.29). The results of principal coordinate analysis (PCoA) showed that myxobacterial addition significantly disturbed the microcosmic microbial community structure (ANOSIM, p < 0.05). LEfSe analysis showed that the relative and absolute abundances (copy numbers) of Bacillus, Pedobacter, Staphylococcus, Streptomyces and Fictibacillus decreased significantly very likely due to myxobacterial predation (p < 0.05). However, the predatory effect of PT13 also increased the relative or absolute abundances of some species, such as Sphingobacterium, Paenarthrobacter, Microbacterium, and Leifsonia. It can be concluded that PT13 has a broad-spectrum lysis spectrum but poor cleavage ability for Streptomyces, and the interaction between complex microorganisms limits the predation effect of PT13 on some prey bacteria. This in turn allows some prey to coexist with myxobacteria. This paper will lay a theoretical foundation for the regulation of soil microecology dominated by myxobacteria.